Transformation of society and social values as economic categories (Economics and region, 2022)
The article summarizes approaches to the analysis of society and social values. The purpose of the article is to substantiate the transformation of society and social values as economic categories. The logical substantiation of the conclusions is carried out using the methods of economic and statistical analysis. The following indicators are analyzed: the rate of change in population both in the world and in Ukraine, trends over the years by age. People's levels of income, economic growth forecasts up to 2100, urbanization and others. Systematization of literature sources and approaches indicates that regardless of the existence of a certain array of scientific and theoretical developments, there is a need to study a range of tools for these categories, typical for both different countries of the world and Ukraine. The urgency of solving the scientific problem lies in the fact that there is currently no single model that would take into account all the factors (or at least most of them) that affect the transformation of society. But such a model would allow better planning for the future period. The study of the issue of systematization and determination of prospects for the transformation of society in the article is carried out in the following logical sequence: characterization of approaches to this in the countries of the world and in Ukraine; formulation of prospects for development and use. Trends in the development of society, and with them the trends in the development of social values, on the one hand, act as generalizing categories, and on the other - affect the development and behavior of each member of this society. The contradictory and ambiguous assessment of changes taking place within society as a whole and within states require constant attention of theorists and practitioners to this object of research. The methodological tools of the study were the method of systematic approach, the method of trends, the selected period of research - 1950-2100 years. The object of the study is all countries of the world, the 25 largest countries in the world in terms of GDP, as well as Ukraine, since it is for these countries that the scientific analysis of the problem under study is presented, which has been formed at the present stage. The study empirically confirms and theoretically proves the transformation of society and social values as economic categories. The tendencies are revealed. The results of the study can be useful for practical use by domestic business entities in the context of choosing optimal business development strategies in different countries (long-term planning), for scientists in the context of the development of scientific research and research of the current state of the problem under study.
Keywords: social development; values; competitiveness; transformation of social values; dynamics